The Effect of Bank Mergers on Loan Prices: Evidence from the United States - Erel, Isil (Review of Financial Studies, 2011)
[Bank mergers can increase or decrease loan spreads, depending on whether the increased market power outweighs efficiency gains. Using proprietary loan-level data for U.S. commercial banks, I find that, on average, mergers reduce loan spreads, with the magnitude of the reduction being larger when postmerger cost savings increase. My results suggest that the relation between spreads and the extent of the market overlap between merging banks is nonmonotonic. The market overlap increases cost savings and consequently lowers spreads, but when the overlap is sufficiently large, spreads increase, potentially due to the market-power effect dominating the cost savings. Furthermore, the average reduction in spreads is significant for small businesses.]